2018
DOI: 10.1111/anu.12841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin C and vitamin E on the growth, antioxidant defence and digestive enzyme activities of juvenile discus fish (Symphysodon haraldi)

Abstract: A 56‐day experiment was carried out to investigate the effects of dietary vitamin C and vitamin E on the growth, antioxidant status and digestive enzyme activities of discus fish (Symphysodon haraldi; initial body weight: 7.96 ± 0.61 g and body length: 5.45 ± 0.65 cm). Animals were fed with 13 different diets including one control diet and 12 treatment diets containing four levels of vitamin C (magnesium‐L‐ascorbyl‐2‐phosphate; 40, 80, 120 and 160 mg/kg) crossed with three levels of vitamin E (DL‐α‐tocopheryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…There is usually a significant relationship between polyphenols and antioxidant activities of plants (Beretta et al, 2017;Liu et al, 2019). In this study, the total phenolic contents of the herbal teas were positively correlated to antioxidant activity measured by DPPH (R 2 =0.956) and H 2 O 2 (R 2 =0.979) with highly significant correlation.…”
Section: Antioxidant Capacitymentioning
confidence: 50%
See 2 more Smart Citations
“…There is usually a significant relationship between polyphenols and antioxidant activities of plants (Beretta et al, 2017;Liu et al, 2019). In this study, the total phenolic contents of the herbal teas were positively correlated to antioxidant activity measured by DPPH (R 2 =0.956) and H 2 O 2 (R 2 =0.979) with highly significant correlation.…”
Section: Antioxidant Capacitymentioning
confidence: 50%
“…Sage and lemon balm have very power antioxidant activity because of rich phenolic components (especially rosmarinic acid) and vitamin C content (Nicolai et al, 2016;Liu et al, 2019). Determination of antioxidant activities of the herbal teas were performed with two common methods DPPH and H 2 O 2 radicals scavenging activities in the present study.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…AA can function independently or in conjugation with vitamin E ( Liu et al, 2019 ). Indeed, AA shows a separate role as an antioxidant due to its high water solubility compared with vitamin E ( Kurutas, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the digestive enzyme activities in the intestine of crucian were the highest when 5% FMLs were added, indicating that the addition of 5% FMLs may promote the activity of digestive enzymes in crucian intestines. We speculated that the digestive enzyme activities in the intestine of crucian may be associated with polysaccharides, folic acid, linoleic acid and other vitamins (Singh & Makkar, 2000), because vitamins promote the activities of digestive enzymes in the intestine of crucian (He et al, 2017;Liu et al, 2019;Qi et al, 2017;Xun et al, 2019), while polysaccharides induce the expression of digestive enzymes (Long et al, 2020).…”
Section: Discussionmentioning
confidence: 99%